Analysis of Inventory Turnover and Return on Equity Ratio on Stock Prices of Miscellaneous Manufacturing Industry Sector Companies Listed on the IDX for the Period 2020-2024 - Gracella Rosnah S Hutagalung; Syahrizal Chalil; Dita Eka Pertiwi Sirait; Artika Wulandari (Journal of Business Inflation Management and Accounting, 2026)
This research aims to study how Inventory Turnover and Return on Equity (ROE) impact stock prices in companies within the miscellaneous manufacturing industry listed on the Indonesia Stock Exchange from 2020 to 2020. This study uses a quantitative approach and is designed as a longitudinal quantitative study. The sample consists of ten companies selected purposively, resulting in 50 panel observations. Secondary data comes from official publications of the Indonesia Stock Exchange (IDX), as well as annual financial reports. The analysis was conducted using a panel data regression model and model selection tests (Chow, Hausman, Lagrange Multiplier), as well as t-tests, F-tests, and the coefficient of determination (R2). The research results indicate that inventory turnover are not significantly affected by stock prices (t-statistic < t-table; p > 0.05), suggesting that during the study period, inventory turnover efficiency was not yet a primary consideration for the market when assessing the value of industry stocks. Conversely, return on equity had a positive impact on stock prices (t-statistic > t-table; p < 0.05), indicating that the market was more responsive to a business's ability to generate profits from its own capital. Inventory Turnover and ROE significantly contribute to the simultaneous variation in stock prices (significant F-test), but the R2 value of 0.3143 indicates that these two variables account for approximately 31.43% of the variation in stock prices, with the remainder influenced by factors outside the model. Beside emphasizing the importance of improving profitability and report transparency for business management.